Technology roadmapping: linking technology resources into business planning. (1st January 2003) - Farrukh, Clare; Phaal, Rob; Probert, David
This paper explores how practical approaches to technology planning can support broadly based valuation decisions within manufacturing companies. A short review of the more traditional approaches to valuing technology is followed by a discussion of practices that are complementary in terms of linking technology, new product development and business planning in the company context. A "fast-start" process for technology roadmapping is proposed as one of these and the latest results from its in-company development are presented. Conclusions are drawn with respect to the contribution of the technique in promoting an inclusive method of obtaining consensus on technology investment.